ANALISIS PELAKSANAAN AKTIVITAS PEMBELAJARAN SOSIOLOGI MELALUI PENGGUNAAN MEDIA GAMES ROLLING BALL DI KELAS XI F2 SMAN 1 SUNGAI BEREMAS - Rahma Nurul Ariska; Yanti Sri Wahyuni; Waza Karia Akbar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning media is a part of education that includes messages, people, and intermediaries. Learning media evolves with the development of technology. Various efforts need to be made by the Sociology teacher to enhance student learning activities, one of which is the relevant Rolling Ball Games media. This media can make student learning activities more active, enjoyable, and interesting. This research aims to describe the analysis of the implementation of sociology learning activities through the use of Rolling Ball Games media in Class XI F2 of SMAN 1 Sungai Beremas. The theory used in this research is the constructivism learning theory, a learning approach that emphasizes the active involvement of students in building and developing their own knowledge. The method used is qualitative. The informants consisted of 12 people: the principal, the deputy head of curriculum, the Class XI sociology subject teacher, and students. The data analysis used is the Miles and Huberman model, with the stages of data collection, data reduction, data display, and conclusion drawing. The results show that there are 3 outcomes carried out by the sociology teacher in enhancing student sociology learning activities through the Rolling Ball Games learning media: (1) The teacher prepares the teaching module at the planning stage of learning (2) The teacher implements learning using the Rolling Ball Games learning media (3) The teacher assesses learning using the Rolling Ball Games media with 3 assessments: cognitive, affective, and psychomotor. The inhibiting factors for the teacher in enhancing learning activities in the classroom are, (1) time constraints and (2) enthusiasm which makes the class atmosphere more active.